Indian constitution - Khosla, Madhav (New Delhi, 2013)
Giving identity to over a billion people, the Indian Constitution is one of the world's great political texts. Drafted over six decades ago, its endurance and operation have fascinated and surprised many. In this short introduction, Madhav Khosla brings to light its many features, aspirations and controversies. How does the Constitution separate power between different political actors? What form of citizenship does it embrace and how can it change? In answering questions such as these, Khosla unravels the document's remarkable and challenging journey, inviting readers to reflect upon the theory and practice of constitutionalism in the world's largest democracy.
Keywords: Constitution-India